Analysis of Limitations in the Mice Tourism Industry of Uganda - Nabiira Nabaale (Uganda Christian University, 2024)
The Mice (meetings, Incentives, Conferences, and Exhibitions) tourism industry in Uganda presents significant potential for economic growth, yet it faces several limitations that hinder its development. The purpose of the study is to investigate the primary constraints affecting the sector, focusing on infrastructure deficiencies, limited marketing strategies , and inadequate policy support limitations in the mice tourism industry in Uganda. This was guided by the following objectives: to examine customer experience analysis, to examine online customer reviews through technology integration and to establish the limitations in the mice tourism industry in Uganda. This study was conducted using a correlational research design with a quantitative approach. The study population consists about 13,000 people. The sample consisted of 30 respondents selected from the target population, 10 questionnaires were answered. This study employed simple random sampling, voluntary response sampling, and convenience sampling techniques to select the sample.The researcher largely used closed-ended questionnaires to collect primary data from the respondents in the sample. In addition to the use of questionnaires, data was collected through observation of the setting and environment of the organization. The reliability and validity of the questionnaire were ensured through a rigorous process. The study found out that positive reviews play a pivotal role in building the mice industry, attracting potential clients, and fostering a positive brand image. Conversely, the presence of negative reviews can lead to hesitations and even deter consumers from making a purchase. Majority ranking demonstrated that most people would not be comfortable purchasing a product or service without reading reviews. In conclusion, the study findings demonstrate that there are limitations in the mice tourism industry of Uganda as demonstrated from the study findings generated. The major recommendation is that tourism and hospitality establishments should increase their presence because travelers today depend on MICE to gain insights into product performance, quality and overall user experience